Additive Manufacturing of 3D Luminescent ZrO2:Eu3+ Architectures. Issue 12 (27th April 2022) - Winczewski, Jędrzej; Herrera, Manuel; Cabriel, Clément; Izeddin, Ignacio; Gabel, Stefan; Merle, Benoit; Susarrey Arce, Arturo; Gardeniers, Han
Abstract: Implementation of more refined structures at the nano to microscale is expected to advance applications in optics and photonics. This work presents the additive manufacturing of 3D luminescent microarchitectures emitting light in the visible range. A tailor‐made organo‐metallic resin suitable for two‐photon lithography is developed, which upon thermal treatment in an oxygen‐rich atmosphere allows the creation of silicon‐free tetragonal ( t ‐) and monoclinic ( m ‐) ZrO2 . The approach is unique because the tailor‐made Zr‐resin is different from what is achieved in other reported approaches based on sol−gel resins. The Zr‐resin is compatible with the Eu‐rich dopant, a luminescent activator, which enables to tune the optical properties of the ZrO2 structures upon annealing. The emission characteristics of the Eu‐doped ZrO2 microstructures are investigated in detail with cathodoluminescence and compared with the intrinsic optical properties of the ZrO2 . The hosted Eu has an orange−red emission showcased using fluorescence microscopy. The presented structuring technology provides a new platform for the future development of 3D luminescent devices. Abstract : Additive manufacturing of 3D luminescent microarchitectures with light emission in the visible range is presented. The 3D europium‐doped zirconia structures (ZrO2 :Eu 3+ ) are produced using two‐photon lithography and tailor‐made resin. The orange−red emission of ZrO2 :Eu 3+ microstructures with sub‐micrometer features is showcased using fluorescence microscopy and studied with cathodoluminescence. The presented structuring technology provides a platform for developing 3D luminescent microdevices.